Efficacy and safety of brivudine for the treatment of herpes zoster: a systematic review and meta-analysis - Jiaxing Chen; Dongyun Lei; Peng Cao; Junchen He; Litao Zhang (Journal of Dermatological Treatment)
Background and objective Brivudine has been used in herpes zoster (HZ) treatment for years, but the safety and efficacy of brivudine are inconclusive. Here we perform a meta-analysis to assess the efficacy, safety, incidence of postherpetic neuralgia of brivudine.Methods Data of randomized controlled Trials (RCTS) were obtained from the databases of both English (PubMed, Embase, and Cochrane Library) and Chinese (China National Knowledge Infrastructure, China Science Journal Database, and WanFang Database) literatures from inception to 12 September 2022. Meta-analyses of efficacy and safety of Brivudine for the treatment of herpes zoster for RCTS were conducted.Results The analyses included seven RCTS (2095 patients in experimental group and 2076 patients in control group) in the treatment of HZ with brivudine. It suggested that the brivudine group was superior to the control group in terms of efficacy (p = .0002) and incidence of postherpetic neuralgia (p = .04). But the incidence of adverse reactions has no significant difference between the brivudine and the control groups (p = .22). In addition, subgroup analysis of adverse events also showed that brivudine was about the same safety as other modalities in the treatment of HZ (p > .05).Conclusions Brivudine is effective for HZ. However, the evidence on the safety of brivudine is insufficient.